Peningkatan Kapasitas Petani dalam Pengelolaan Tanah Masam melalui Pelatihan JADAM Liquid Fertilizer (JLF) Berbasis Bahan Lokal di Desa Punan Dulau Kecamatan Sekatak, Kabupaten Bulungan - Danil DANIL; Rina Lesmana; Marian Usmani Putra; Akhmad Rafi'i; Bansir Bansir (CV. ITTC INDONESIA, 2026)
Punan Dulau Village, Sekatak District, Bulungan Regency, has considerable agricultural land potential; however, limited farmer knowledge regarding soil pH management and dependence on chemical fertilizers remain challenges to improving land productivity. This community service program aimed to strengthen farmers’ capacity through socialization and hands-on training on the preparation of JADAM Liquid Fertilizer (JLF) as a locally based organic fertilizer alternative. The activity involved 35 farmers and applied an educative-participatory approach through interactive lectures, discussions, and practical demonstrations. Evaluation was conducted descriptively through observation and participant feedback. The results indicated an improvement in farmers’ understanding of soil management, enhanced technical skills in producing and applying JLF, and increased willingness to adopt locally sourced organic inputs. The program contributed to promoting more efficient, environmentally friendly, and sustainable agricultural practices.